Structural basis for ion selectivity revealed by high-resolution crystal structure of Mg2+ channel MgtE - CAFFREY, MARTIN (My University, 2014)
Magnesium is the most abundant divalent cation in living cells and is crucial to several biological processes. MgtE is a Mg 2 þ channel distributed in all domains of life that contributes to the maintenance of cellular Mg 2 þ homeostasis. Here we report the high- resolution crystal structures of the transmembrane domain of MgtE, bound to Mg 2 þ ,Mn 2 þ and Ca 2 þ . The high-resolution Mg 2 þ -bound crystal structure clearly visualized the hydrated Mg 2 þ ion within its selectivity filter. Based on those structures and biochemical analyses, we propose a cation selectivity mechanism for MgtE in which the geometry of the hydration shell of the fully hydrated Mg 2 þ ion is recognized by the side-chain carboxylate groups in the selectivity filter. This is in contrast to the K þ -selective filter of KcsA, which recognizes a dehydrated K þ ion. Our results further revealed a cation-binding site on the periplasmic side, which regulate channel opening and prevents conduction of near-cognate cations.
PUBLISHED
Keywords: Magnesium; Magnesium